O ensino do conceito de densidade em ciências do ensino fundamental - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This paper describes and analyzes a teaching unit developed in Science classroom of Basic Education, aiming at the formation of the concept of density by students in a class of nineth grade of elementary school in a public school, located at Caçapava do Sul, RS. To theoretically support this work, we used the historical-cultural theory of Lev Vygotsky, in order to explain the formation of the scientific concept of density by students, and the principle of education through research to stimulate the reconstruction of knowledge of students with the consequent adoption of research as everyday attitude. The teaching unit was divided in two stages. The first stage includes the process, during which he encouraged the interaction between students and between them and the teacher, for the development of their of proximal development zone, through experimental measurements and activities, so that they could reach the concept of density. The second stage, illustrates how students can conduct research about the many scientific usages of the word density in science. This teaching unit was developed in eight meetings totalizing twenty hours class. The analysis of data obtained from this work was qualitatively done using instruments like the recordings of lessons, observations recorded during various applied activities, the students and teacher’s logbook. The teaching unit resulted in educational production in the form of an Activity Guide for Teachers, which provides guidance for use in the classroom. The Guide contains a description of how to develop the activities and equipment necessary for its implementation.
Keywords: Educação; Densidade; Unidade didática; Experimentação; Ensino fundamental; Education; Density; Teaching unit; Experimentation; Elementary school